2021
DOI: 10.1590/1677-5449.200143
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of the muscle O2 resaturation parameters most used for assessing reactive hyperemia: a near-infrared spectroscopy study

Abstract: Background There is a spectrum of possibilities for analyzing muscle O2 resaturation parameters for measurement of reactive hyperemia in microvasculature. However, there is no consensus with respect to the responsiveness of these O2 resaturation parameters for assessing reactive hyperemia. Objectives This study investigates the responsiveness of the most utilized muscle O2 resaturation parameters to assess reactive hyperemia in the microvasculature of a clinical group known to exhibit impairments of tissue O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In their study, Soares et al (2019) showed that after 5 min occlusion at 250 mmHg at the arm, the NIRS reperfusion slope calculated for the forearm (flexor digitorum superficialis muscle) showed a value of 1.77 ± 0.60%•s −1 for TSI% [41], which is slightly higher than our findings for G3 (1.37 ± 0.33%•s −1 ). On the flexor carpi radialis muscle, a reoxygenation rate of 1.24 ± 0.41%•s −1 was found after 5 min occlusion at 250 mmHg [42], and, interestingly, results on leg measurements match our findings on forearm measurements, with 1.32 ± 0.38 [24] and 1.60 ± 0.80%•s −1 [27] for tibialis anterior.…”
Section: Reliability Of Reoxygenation Ratessupporting
confidence: 87%
“…In their study, Soares et al (2019) showed that after 5 min occlusion at 250 mmHg at the arm, the NIRS reperfusion slope calculated for the forearm (flexor digitorum superficialis muscle) showed a value of 1.77 ± 0.60%•s −1 for TSI% [41], which is slightly higher than our findings for G3 (1.37 ± 0.33%•s −1 ). On the flexor carpi radialis muscle, a reoxygenation rate of 1.24 ± 0.41%•s −1 was found after 5 min occlusion at 250 mmHg [42], and, interestingly, results on leg measurements match our findings on forearm measurements, with 1.32 ± 0.38 [24] and 1.60 ± 0.80%•s −1 [27] for tibialis anterior.…”
Section: Reliability Of Reoxygenation Ratessupporting
confidence: 87%
“…As a result, by-products from the energetic metabolism can induce microvascular vasodilation, increasing the blood flow velocity in the upstream artery, which results in an increased FMD response. A previous study from our Laboratory failed to show a correlation between the brachial artery FMD and muscle StO 2 parameters during ischemia [ 10 ]. These divergent findings reinforce that the macro and microvascular response observed in the brachial artery should not be extrapolated to the other arteries present in the body’s other segments (i.e., lower limb).…”
Section: Discussionmentioning
confidence: 99%
“…From a mechanical perspective, the magnitude of ischemia induced by cuff occlusion depends on the oxidative capacity of muscles experiencing oxygen deprivation. When a muscle extracts a high oxygen level during cuff occlusion, a more robust magnitude of ischemia is generated [ 10 , 17 ]. As a result, by-products from the energetic metabolism can induce microvascular vasodilation, increasing the blood flow velocity in the upstream artery, which results in an increased FMD response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations